Reducing Risk in Total Joint Arthroplasty: Assessing Mental Health, Mood, and Movement Disorders. Issue 3 (September 2019) - Keswani, Aakash; Chen, Darwin
Abstract : Preoperative and postoperative mental health status (MHS) of total joint arthroplasty patients can affect immediate and long-term outcomes following surgery. Alterations in MHS can be acute or chronic. The most common etiologies include acute changes due to (1) delirium or stroke, (2) movement disorders (Alzheimer dementia, Parkinson disease, multiple sclerosis, epilepsy), and (3) mood/behavior disorders (major depressive disorder, anxiety, bipolar disorder, schizophrenia). Across etiologies, alterations in MHS are associated with worse clinical/patient-reported outcomes and greater total cost of care. Prevention via pharmacologic and nonpharmacologic approaches is the cornerstone of management for changes in MHS due to postoperative delirium/stroke. Parkinson disease, multiple sclerosis, and epilepsy must be addressed presurgery and postsurgery via tailored care pathways to minimize complications, limit disease progression, and ensure maximal functional recovery. Major depressive disorder, anxiety, bipolar, and schizophrenia require screening and proactive, longitudinal treatment where from all members of the care team. Beyond reviewing outcomes impact and management of MHS-altering conditions in arthroplasty patients, we provide a framework for evidence-based interventions organized by disease-type to enable effective perioperative optimization and postoperative care for these patients.